Using Banach Fixed Point Theorem To Study The Stability Of First-Order Delay Differential Equations - Zaid A. A. Mahdi Monje; Buthainah A. A. Ahmed (Al-Nahrain Journal of Science, 2020)
In1 this1 paper1 we1 use the Banach fixed point theorem investigate 1the stability and asymptotic1 stability1 of the zero solution for the first order retarded delay differential equation 1(y(t)) ́=-∑_(j=1)^N▒〖b_j (t ,〖3y〗_t )3y(t)+f(t ,〖3y〗_t)〗 where the delay is constant. Also we give new conditions to ensure the stability and asymptotic stability of the zero solution of this equation.